2012
DOI: 10.1111/j.1365-2516.2012.02791.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in haemophilia A: Hemophilia Utilization Group Study Va (HUGS‐Va)

Abstract: This study describes health-related quality of life (HRQoL) of persons with haemophilia A in the United States (US) and determines associations between self-reported joint pain, motion limitation and clinically evaluated joint range of motion (ROM), and between HRQoL and ROM. As part of a 2-year cohort study, we collected baseline HRQoL using the SF-12 (adults) and PedsQL (children), along with self-ratings of joint pain and motion limitation, in persons with factor VIII deficiency recruited from six Haemophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 31 publications
7
85
0
6
Order By: Relevance
“…Details of the study methods and inclusion criteria have previously been reported. 6 , 7 Informed consent and data were collected at initial interview from participant/parent selfor proxy-report and patient chart reviews completed by healthcare providers. Information regarding clinical aspects of the disease, such as treatment regimen, arthropathy and comorbidities, as well as HrQoL and the economic consequences of having hemophilia A, were collected.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the study methods and inclusion criteria have previously been reported. 6 , 7 Informed consent and data were collected at initial interview from participant/parent selfor proxy-report and patient chart reviews completed by healthcare providers. Information regarding clinical aspects of the disease, such as treatment regimen, arthropathy and comorbidities, as well as HrQoL and the economic consequences of having hemophilia A, were collected.…”
Section: Datamentioning
confidence: 99%
“…Baseline HrQoL and its association with joint pain and motion limitation in the HUGS Va population has previously been reported. 7 The current analysis includes data from 261 participants (136 adults and 125 children) who completed their initial interview and at least one follow-up, out of a total of 329 participants (164 adults and 165 children) with factor VIII deficiency who were recruited into the HUGS Va study between July 2005 and July 2007.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Although joint deterioration continues to exist, it is not such a clearly determining factor in their perceived quality of life as it is in other aspects [6,11,15]. In these patients, the development of inhibitors leads to greater difficulties in managing in their surroundings and integrating into society [31,32].…”
Section: Quality Of Lifementioning
confidence: 99%
“…Some studies [5,6] have described how haemorrhages and the physical sequelae of haemophilia not only affect physical functions but are also a threat to patients' psychological and social well-being, and may affect their quality of life.…”
Section: Introductionmentioning
confidence: 99%